Isolation of Terrabacter sp. Strain DDE-1, Which Metabolizes 1,1-Dichloro-2,2-Bis(4-Chlorophenyl)Ethylene when Induced with Biphenyl - Aislabie, J. (American Society for Microbiology, 1999)
Terrabacter sp. strain DDE-1, able to metabolize 1,1-dichloro-2,2-bis(4-chlorophenyl)ethylene (DDE) in pure culture when induced with biphenyl, was enriched from a 1-1-1-trichloro-2,2-bis(4-chlorophenyl)ethane residue-contaminated agricultural soil. Gas chromatography-mass spectrometry analysis of culture extracts revealed a number of DDE catabolites, including 2-(4′-chlorophenyl)-3,3-dichloropropenoic acid, 2-(4′-chlorophenyl)-2-hydroxy acetic acid, 2-(4′-chlorophenyl) acetic acid, and 4-chlorobenzoic acid.